Factors related to the way of giving MP-ASI to Infants aged 6-12 Months in Bonesompe Village, Lawanga Community Health Center, Poso Regency - Rusmiati Nurrjanah; Budiman Budiman; Eka Prasetia Hati Baculu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Supplement food os ASI (mother’s breast milk) or MP-ASI is additional food that was given to the baby besides ASI after the baby has been six months old until twelve months old. Supplement food ASI is given to fulfill the need for energy and nutrient substances for a baby who has insufficient ASI. Supplement food ASI is a transitional process from only basic milk food toward semi-common food. This research used the analytical design and approach of Cross-Sectional Study. The population of this research is all 45 women who have babies of 6 to 12 months old at Kelurahan Bonesompe. The sample which was used is the Total Sampling technique. The test which was used in this research is Chi-Square Test. Research findings show that there is a significant correlation between women's or mothers' knowledge and MP-ASI feeding with p-value = 0,03 (p,< 0,05) and there is also a correlation between education and MP-ASI feeding with p-value = 0,02 ( p< 0,05). This research suggested women or mother of family at Kelurahan Bonesompe of Poso Regency to comprehend feeding of ASI supplement food for a baby who has been six months old because a part of MP-SI help meets the need of nutrient toward the baby.